Press statement: emergency resolution on Spain
015a_0039_001 'For The Press. EMERGENCY RESOLUTION. This Congress, representing the organised workers of Great Britain,profoundly moved by the heroic struggle of the Spanish people for the maintenance of freedom and democracy, endorses the declarations already made on behalf of the British Labour Movement, and sends its warmest fraternal greetings to our respected comrade and Trade Union colleague, Largo Caballero, as Head of the new Spanish Government. In the confident assurance that they embody the unconquerable Will of the Spanish nation to defeat the forces of Fascism and tyranny we pledge afresh our utmost support to the Spanish people. 292/946/15a/39